Using Appropriate Assessment to Plan Braille Literacy Instruction. (May 2022) - Stewart, Robin; Zebehazy, Kim T.; Holbrook, M. Cay
To be effective teachers of literacy for students who read braille, we need to know what our students' strengths and needs are as all these components come together in braille literacy. Using an appropriate assessment that addresses the skill sets involved in braille literacy is critical to putting together effective intervention packages for our students. The first author used the Kamei-Hannan and Ricci Reading Assessment (2015) and the Braille Reading Analysis Chart (Harley, et al., 1997) to determine areas of need for a student in grade 2 in a braille literacy program. Needs included: identifying ending sounds and naming final letters and sounds; basic decoding of short and long vowel sounds; recognizing sight words; and identifying letters. Specific miscue patterns in tactile perception (reversals) were identified. Information gathered from these assessments was used to develop a targeted intervention package and informed the development of a balanced literacy program for this student. Following a period of implementation, data showed evidence of overall improvement in braille literacy skills.